-k(x-1)+2kx=1

Simple and best practice solution for -k(x-1)+2kx=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -k(x-1)+2kx=1 equation:


Simplifying
-1k(x + -1) + 2kx = 1

Reorder the terms:
-1k(-1 + x) + 2kx = 1
(-1 * -1k + x * -1k) + 2kx = 1
(1k + -1kx) + 2kx = 1

Combine like terms: -1kx + 2kx = 1kx
1k + 1kx = 1

Solving
1k + 1kx = 1

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Reorder the terms:
-1 + 1k + 1kx = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + 1k + 1kx = 0

The solution to this equation could not be determined.

See similar equations:

| 18.7-15.1b=-17.4b-19.02 | | x/.010 | | 8x+8=17x-3 | | -7.7p=-8.5p-11.2 | | -9r+17=-14-20-12r | | -8h+18=-10h | | X=ln21/ln8 | | 3k+m=10 | | 1+2c=4c+19 | | 5-3(4-2x)+3-2(5-x)=0 | | 4/5k=5/2 | | -8t=-13+20 | | Kx-k=1 | | -18m+1=-m+20-18m | | 23x+1=22x+4 | | -14-8n=18-16n | | 4s=-10+5s | | -3v-5=6v-5 | | 9+2z+9z=-1+10z | | -3d=-8-7d | | 2w+6=-2-10 | | 2(x-1)-3(3x+2)+4(x+2)=0 | | -2y+5+3y=5y+5 | | .5b+4=20 | | -10-5g=8+4g | | 5(2l+3)=95 | | 10j+2=9j+10 | | (x+19)=(7x-8) | | q=9+2q | | 5k+9=4K | | -2k+4m=-9 | | 10u-3=9u-6 |

Equations solver categories